Alternative usage of miRNA-biogenesis co-factors in plants at low temperatures - Ré, Delfina Adela (2019)
Plants use molecular mechanisms to sense temperatures, trigger quick adaptive responses and thereby cope with environmental changes. MicroRNAs (miRNAs) are key regulators of plant development under such conditions. The catalytic action of DICER LIKE 1 (DCL1), in conjunction with HYPONASTIC LEAVES 1 (HYL1) and SERRATE (SE), produces miRNAs from double-stranded RNAs. As plants lack a stable internal temperature to which enzymatic reactions could be optimized during evolution, reactions such as miRNA processing have to be adjusted to fluctuating environmental temperatures. Here, we report that with decreasing ambient temperature, the plant miRNA biogenesis machinery becomes more robust, producing miRNAs even in the absence of the key DCL1 co-factors HYL1 and SE. This reduces the morphological and reproductive defects of se and hyl1 mutants, restoring seed production. Using small RNA-sequencing and bioinformatics analyses, we have identified specific miRNAs that become HYL1/SE independent for their production in response to temperature decrease. We found that the secondary structure of primary miRNAs is key for this temperature recovery. This finding may have evolutionary implications as a potential adaptation-driving mechanism to a changing climate.